Restoring of fast neutron energetic spectra on the basis of amplitude distribution of signals measured by single crystal neutron spectrometer - Olejnik, S.N.; Shlyakhov, N.A.; Bozhko, V.P. (Вопросы атомной науки и техники, 2000)
The technique of restoring fast neutron spectra on the basis of amplitude spectra registered by a scintillation detector has been developed. The typical instability of restoring, that is boundary ejection and periodic perturbations, has been found out. The quality criteria of restoring, such as values of empirical risk and conditional characteristics of a matrix in the set of linear equations have been proposed. The main reasons of solution instabilities and methods of their overcoming have been found.